Ultraviolet All-Optical Switching via Zinc Oxide Thin Films - Smith, Trenten Andrew; Haeuser, Samuel J; King, Seth T; Gansen, Eric J (Proceedings of the Wisconsin Space Conference, 2020)
Zinc oxide (ZnO) is a semiconductor material exhibiting a wide bandgap in the ultraviolet (UV) region. ZnO is a promising material for use in short-wave optoelectronic devices such as all-optical switches (AOSs). Our switch is composed of a polycrystalline ZnO thin film grown by DC sputter deposition and uses a 120ps control pulse tuned to the band edge of the film to modify the transmission of a weaker signal pulse. The signal light is heavily absorbed in the absence of the control pulse, representing an off state of the switch. The control pulse, when incident on the film, resonantly excites electrons to create excitons. This decreases the material’s absorption by filling energy states and screening the built-in electric field of the ZnO. Consequently, more signal light is transmitted by the film, representing an on state.